GAYA KEPEMIMPINAN KEPALA RUANGAN DENGAN PEMBERDAYAAN PSIKOLOGIS PERAWAT PELAKSANA - Demur, Dia Resti Dewi Nanda; Endang, Lola Gus; Yuliano, Aldo (Jurnal Kesehatan Medika Saintika, 2024)
Psychological empowerment is a sense of confidence that individuals are able to carry out work activities according to the expected abilities and competencies. The fact is that nurses feel unappreciated for their work, always considered wrong, not included in decision making. The purpose of this study was to determine the relationship between the leadership style of the Head of the Room and the psychological empowerment of Nurses. The research method was descriptive analytical with a cross-sectional design. The study was conducted at Dr. MA Hanafiah SM Batusangkar Hospital. The population was 200 nurses. A sample of 67 people was taken proportionally using stratified random sampling. Data collection was carried out by filling out a questionnaire, then processed and analyzed using the chi-square test. Univariate analysis showed that 70.1% of respondents stated that the leadership style of the head of the room was democratic and 64.2% stated that there was psychological empowerment of nurses. Bivariate results showed that there was a relationship between the leadership style of the head of the room and the psychological empowerment of nurses at Prof. Dr. MA Hanafiah Batusangkar Hospital (p = 0.001). It was concluded that the leadership style of the head of the room was related to the psychological empowerment of nurses. It is recommended that the head of the room apply the right leadership style and appreciate his subordinates, so that he can increase the psychological empowerment of implementing nurses.Keywords: leadership style; psychological empowerment